The Effectiveness of Bowen's Intergenerational Therapy-Based Training and the McMaster Model in Improving Anxiety, Self-Efficacy, and Self-Control of Men and Women on the Verge of Divorce - Delfanazari, Ramin; Behbodi, Masoumeh; Dokaneifard, Farideh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the effectiveness of Bowen's intergenerational therapy and compare it with the McMaster model on anxiety, self-efficacy, and self-control of men and women on the verge of divorce. Methods: The present study was quasi-experimental with pre-test and post-test and the control group with a two-month follow-up. The statistical population consisted of men and women who visited counseling centers in District 6 of Tehran in 2020. After screening with Zank Anxiety Scale (1971), 45 men and women were selected by convenience method and were randomly assigned to experimental groups of Bowen's intergenerational model (n=15), experimental group of McMaster model (n=15), and the control group (n=15). Both experimental groups underwent Bowen's intergenerational model (1981) and McMaster model (2007) interventions for eight 90-minute sessions, and the control group did not receive any intervention. The research tools included the general self-efficacy scale by Sherer and Maddux (1982), and the self-control Scale by Tangney, Bamster, and Boone (2004). The data were analyzed using the mixed model repeated-measures analysis of variance. Results: The results indicated the effect of Bowen's intergenerational intervention on scores of anxiety (F=5.73, P=0.024), self-efficacy (F=6.16, P=0.019), and self-control (F=9.24, P=0.005), and also the McMaster model intervention on scores of anxiety (F=5.25, P=0.030), self-efficacy (F=8.56, P=0.007), and self-control (F=8.56, P=0.007), and the stability of the effects at the follow-up stage. Conclusion: The results of the study indicated that Bowen's intergenerational intervention and McMaster model were suitable methods to increase self-efficacy and self-control and decrease anxiety in women and men with marital conflict and on the verge of divorce.